41 UMP staff receives zakat - Nor Salwana, Mohammad Idris (2020)
Pekan, 24 September 2020 - Concerned with the welfare of its staff, Yayasan Universiti Malaysia Pahang (UMP) has acted proactively by channelling zakat assistance to 41 staff who are eligible to receive zakat.